Maxwell's guide to authority work - Maxwell, Robert L. (American Library Association, 2002)
Written for library administrators and catalogers, this guide lists the key components of authority work and provides instructions for preparing a complete authority record. Chapters concentrate on standards, control procedures, names, titles, series, thesaurus building, subjects, genres, and cooperative programs. Particular attention is give to the procedures for creating uniform access points, record-keeping, and sharing information.